Which dimensional model for the analysis of a coated tube adsorber for adsorption heat pumps? - Dias, João M. S. (2021)
This paper presents the analysis of a coated tube adsorber for adsorption heat pumps (AHP), starting from a well-established physical model and providing information on how many dimensions need to be considered for a given accuracy. A lumped-parameter model, one-dimensional (radial direction) and two-dimensional (radial and longitudinal directions) distributed-parameter models describing the adsorber's dynamics are discussed. The optimal resolution, guaranteeing an accuracy of ≈1% with lower computational efforts is identified. Results obtained with the three dimensional models are compared and their suitability to predict the coefficient of performance (COP) and the specific heating power (SHP) of an AHP is investigated. Results show that the lumped-parameter model is able to predict the COP with minor deviations from the reference model; however, the SHP is overestimated. Furthermore, several sensibility analyses are performed aiming to assess the influence of important parameters, such as the adsorber tube length and heat transfer fluid's (HTF) velocity. In addition, the influence of disregarding the adsorber metal tube mass is evaluated, resulting in deviations up to ≈4.5% for the COP and ≈7% for the SHP, which are considered significant. Results guide researchers to adopt a given dimensional model for the required accuracy.